Rainband feature tracking for wind speeds around typhoon eyes using multiple sensors. Issue 9 (2nd May 2016) - He, Shuangyan; Liu, Antony K.; Yu, Cheng-Ku; He, Zhiguo; Yang, Jingsong; Zheng, Gang; Chen, Ying
Abstract : In this article, five typhoon cases observed by quasi-concurrent satellite-based synthetic aperture radar (SAR) and Moderate Resolution Imaging Spectroradiometer (MODIS) were studied with a feature-tracking technique. The rainband features around typhoon eyes were first delineated using wavelet analysis, and then the wind speeds were estimated by feature tracking using quasi-concurrent multi-sensor images. It was found that the feature tracking-estimated wind speeds are reasonable compared with the maximum wind speed reported by the Joint Typhoon Warning Center (JTWC), which accounts for the radial dependence of wind speed using the Rankine combined vortex approximation. In a specific case, with the aid of Doppler radar observations near the northern coast of Taiwan, wind speed estimation based on the multi-sensor also shows consistent results. This study demonstrates that the local wind distribution of cyclonic winds around typhoon eyes at different radial distances from the typhoon centres may be derived from rainband feature tracking using quasi-concurrent multi-sensor images. This technique may offer useful wind information for typhoon simulations and forecasting.